The 2018 failed outburst of H 1743 – 322: Insight-HXMT, NuSTAR, and NICER views. Issue 3 (22nd March 2022) - Wang, P J; Kong, L D; Chen, Y P; Zhang, S; Zhang, S N; Soria, R; Ji, L; Qu, J L; Huang, Y; Tao, L; Ge, M Y; Lu, F J; et al.
ABSTRACT: We studied the 2018 outburst of the black hole transient H 1743 − 322 with a series of Insight-HXMT, NICER, and NuSTAR observations, covering the 1–120 keV band. With our broad-band X-ray spectral modelling, we confirm that the source remained in the low/hard state throughout the month-long outburst, although it became marginally softer at peak flux. We detected Type-C quasi-periodic oscillations (QPOs) and followed the evolution of their properties. The QPO frequency increased from ∼0.1 to ∼0.4 Hz during the rising phase of the outburst and decreased again in the decline. Continuum X-ray flux, power-law photon index, QPO frequency, and QPO root-mean-square amplitude were positively correlated. The QPO amplitude was slightly higher in the soft X-ray band (typical values of 12–16 per cent, compared with 8–10 per cent in the hard band). Our spectral-timing results shed light on the initial rising phase in the low/hard state, which has rarely been monitored with such high cadence, time resolution, and broad-band coverage. Combining spectral and timing properties, we find that 'failed' (hard state only) and 'successful' outbursts follow the same initial evolutionary track, although the former class of outburst never reaches the threshold for a transition to softer (thermally dominated) accretion regimes.